The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1109/jiot.2018.2872431
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Resonant Beam Charging for Electronic Vehicles in Internet of Intelligent Vehicles

Abstract: To enable electric vehicles (EVs) to access to the internet of intelligent vehicles (IoIV), charging EVs wirelessly anytime and anywhere becomes an urgent need. The resonant beam charging (RBC) technology can provide high-power and long-range wireless energy for EVs. However, the RBC system is unefficient. To improve the RBC power transmission efficiency, the adaptive resonant beam charging (ARBC) technology was introduced. In this paper, after analyzing the modular model of the ARBC system, we obtain the clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 22 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…Another compelling technology is distributed laser charging (DLC), known also as resonant beam charging (RBC), has recently been proposed and studied 11,12 . It is shown that RBC is capable of transmitting a wireless power of approximately 2W over a distance up to 10 m 13 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Another compelling technology is distributed laser charging (DLC), known also as resonant beam charging (RBC), has recently been proposed and studied 11,12 . It is shown that RBC is capable of transmitting a wireless power of approximately 2W over a distance up to 10 m 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The end‐to‐end transmission efficiency of both conventional and adaptive RBC systems were studied in previous works 2,11,12,14–16 . Also, scheduling algorithm for multi‐user RBC system was presented in Fang et al 11,17 and Liu et al 18 Multiple access techniques for WPT applying quality of charging service (QoCS) and charging pricing strategy (CPS) for WPT system was studied in Liu et al, 18 Fang et al, 19 and Xiong et al 20 Furthermore and to overcome the echo interference affecting RBC‐SWIPT, optical filtering and frequency shifting methods were proposed in Xiong et al 21,22 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations